2020
DOI: 10.1016/j.jds.2019.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Ossifying fibroma of the jaw bones in hyperparathyroidism-jaw tumor syndrome: Analysis of 24 cases retrieved from literatures

Abstract: Background/purpose Hyperparathyroidism-jaw tumor syndrome is a rare autosomal dominant disease characterized by parathyroid tumors and ossifying fibroma of the jaw. Disease-causing mutations have been localized in the tumor suppressor gene CDC73. This study is designed to highlight the importance of genetic testing in the diagnosis of ossifying fibroma related to this syndrome. Materials and methods The Clinical, histopathological, radiographical, familial and genetic f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 35 publications
0
17
0
2
Order By: Relevance
“…However, the penetrance rate of jaw is likely to be underestimated, because some patients in whom the OF develop before the HPT may not be correlated with HPT-JT. In HPT-JT patients with presentation of jaw tumor, 25% of the jaw tumor precede the development of HPT [ 31 ]. On the other hand, diagnosis of OF in the jaw is particularly challenging for the pathologist, and may be misdiagnosed as OD or FD.…”
Section: Discussionmentioning
confidence: 99%
“…However, the penetrance rate of jaw is likely to be underestimated, because some patients in whom the OF develop before the HPT may not be correlated with HPT-JT. In HPT-JT patients with presentation of jaw tumor, 25% of the jaw tumor precede the development of HPT [ 31 ]. On the other hand, diagnosis of OF in the jaw is particularly challenging for the pathologist, and may be misdiagnosed as OD or FD.…”
Section: Discussionmentioning
confidence: 99%
“…The youngest age at presentation for HPT-JT syndrome reported in the literature is 10 years [ 8 ]. In a study conducted by Le Collen et al, a family carrier of CDC73 gene exon 3 deletion was reported characterized by hypercalcemia, renal deterioration, and atypical parathyroid adenomas [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Oral and dental surgeons must be aware of the possibility of HPT-JT syndrome in adolescents and young adults who present with a jaw mass and high serum PTH levels, either as an independent clinical entity or in conjunction. Keeping in view the patient’s clinical presentation, here comes the role of detailed probing of the patient’s family history and genetic analysis for CDC73 genetic mutation [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…CDC73 gene encodes for an evolutionary conserved protein, known as parafibromin 8,12 . This protein consists of 531 amino acids, is predominantly expressed in the nucleus of the cells and can be found in many tissues of the human body such as parathyroid and adrenal glands, kidneys, heart, hypophysis and skeletal muscles 8,18,19 . Parafibromin shows off strong anti-proliferative properties and is a component of Polymerase-Associated Factor 1 complex (PAF1c) that includes, overall, five more proteins 17,20 .…”
Section: Cdc73 Genementioning
confidence: 99%
“…In spite of the denomination of the syndrome, jaw tumors are found in approximately 30-40% of the affected patients 7,14,19 . These are called ossifying fibromas and, by definition, are benign, slow growing masses that histologically consist of avascular fibroblastic stroma with spindled neoplastic cells that produce various amounts of aberrant mineralized and cementum-like material (Figure 1) 19,22 . In…”
Section: Jaw Tumorsmentioning
confidence: 99%